Living off Sociology: Graduates from Universidad Nacional de Colombia and Labor Market Segments - Beltrán Cely, William Mauricio; Berrío Gil, Darío (Sociedad y Economía, 2016)
This paper gathers and assesses some information, from the perspective of labor marketsegmentation, regarding the jobs graduates from the Department of Sociology at Universidad Nacional de Colombia are hired for. A cohort based on the graduation year was built, being the time lapse considered 2000 to 2010. When surveyed and interviewed,graduates were required to tell about their first and current job employer, type of laborand labor conditions. According to the results, graduates are employed mainly in fourlabor market segments: teaching, research, consultancy, and social service. The positionsoccupied on the first job involved a wider variety of activities than those in the last one,and labor conditions seem to improve.